Investigating effective wayfinding in airports: a Bayesian network approach - Farr, Anna C.; Kleinschmidt, Tristan; Johnson, Sandra; Yarlagadda, Prasad K. D. V.; Mengersen, Kerrie (Transport, 2014)
Effective wayfinding is the successful interplay of human and environmental factors resulting in a person successfully moving from their current position to a desired location in a timely manner. To date this process has not been modelled to reflect this interplay. This paper proposes a complex modelling system approach of wayfinding by using Bayesian Networks to model this process, and applies the model to airports. The model suggests that human factors have a greater impact on effective wayfinding in airports than environmental factors. The greatest influences on human factors are found to be the level of spatial anxiety experienced by travellers and their cognitive and spatial skills. The model also predicted that the navigation pathway that a traveller must traverse has a larger impact on the effectiveness of an airport’s environment in promoting effective wayfinding than the terminal design. First Published Online: 25 Mar 2014